FST548: Food Processing Technology / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2023)
This course will provide students with the theoretical aspects of food product manufacturing. This syllabus covers manufacturing of selected food commodities and the quality control of the finished products. Students are also required to identify, detect and solve problems related to food manufacturing processes. Knowledge transfer programme to the community, which is designed in this subject will help students to improve their soft skills.